2008
DOI: 10.1073/pnas.0800178105
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-92 cluster accelerates adipocyte differentiation by negatively regulating tumor-suppressor Rb2/p130

Abstract: Adipogenesis involves cell proliferation and differentiation, both of which have been shown to be regulated by micro (mi)RNA. During mouse preadipocyte 3T3L1 cell differentiation, we found that miR-17-92, a miRNA cluster that promotes cell proliferation in various cancers, was significantly up-regulated at the clonal expansion stage of adipocyte differentiation. Stable transfection of 3T3L1 cells with miR-17-92 resulted in accelerated differentiation and increased triglyceride accumulation after hormonal stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
247
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(264 citation statements)
references
References 25 publications
9
247
0
5
Order By: Relevance
“…We show that it causes a modest caspase activation in 3T3-L1 cells that does not result in a long term cell mortality as confirmed by the absence of effect on postclonal expansion, a phenomenon reported to be necessary for the differentiation of 3T3-L1 cells (33). It is known that during adipocyte differentiation, the early expression of C/EBP␤ induces C/EBP␣ and PPAR␥ (34), which are responsible for the coordinated regulation of expression of several genes leading to terminal differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…We show that it causes a modest caspase activation in 3T3-L1 cells that does not result in a long term cell mortality as confirmed by the absence of effect on postclonal expansion, a phenomenon reported to be necessary for the differentiation of 3T3-L1 cells (33). It is known that during adipocyte differentiation, the early expression of C/EBP␤ induces C/EBP␣ and PPAR␥ (34), which are responsible for the coordinated regulation of expression of several genes leading to terminal differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…As a potential mechanism of cancer cell cycle regulation by miR-17-92, it was reported that c-mycinduced miR-17 and miR-20a cooperate with the RB/E2F signaling pathway to control the accurate timing of the G 1 /S transition [18] . Cloonan et al reported that miR-17-5p regulates more than 20 G 1 /S transition-related genes [19] , and RBL2 was identified as a functional downstream gene of miR-17-5p [20,21] . It should be noted that the targets of miR-17-92 depended on the cellular context, which results in diverse functions of the miR-17-92 cluster in different cells.…”
Section: Let-7 Familymentioning
confidence: 99%
“…It has been reported that the miR-17-92 cluster is frequently amplified [14,15] , and let-7 is frequently down-regulated [9,104] in various cancers. miR-17-92 exerts oncogenic functions through positively regulating cell cycle-related proteins, including p21, p63, p57, and RBL2 [18][19][20][21] , whereas let-7 exerts its tumor suppressive function by down-regulating RAS, cyclins and CDK4 [8][9][10][11] . miR-21 is activated by RAS signaling and suppressed by several negative regulators of RAS signaling and the PI3K/AKT pathway, which in turn potentiates RAS activation and PI3K/AKT activities [72] .…”
Section: Implications Of Cell Cycle-related Mirnas In Anti-cancer Thementioning
confidence: 99%
“…Emerging evidence has suggested that a number of miRNAs are important in the regulation of adipocyte differentiation, including the miR-143 (9) and miR-1792 clusters (10). miR-26b is an intronic miRNA encoded in the carboxy-terminal domain, RNA polymerase II, polypeptide A, small phosphatase 1 (CTDSP1) gene that is important in a variety of different diseases, including lung carcinoma, breast cancer and cardiac hypertrophy (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%